2017
DOI: 10.1016/j.eurpolymj.2017.07.037
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric relaxation mechanisms in polyoxymethylene/polyurethane/layered silicates hybrid nanocomposites

Abstract: Polyoxymethylene/Polyurethane/Layered Silicates (POM/PU/LS) ternary hybrid nanocomposites were prepared by two methods: (a) direct melt compounding (DM) and (b) melt compounding using a latex-mediated masterbatch (MB) technique. The morphology of the produced specimens and the quality of the dispersion of LS (synthetic sodium fluorohectorite) were examined via Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM). Broadband dielectric spectroscopy (BDS) was employed in order to study th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
(76 reference statements)
0
5
0
Order By: Relevance
“…universality law” may be used to characterize the typical behavior of AC conductivity in disordered solids and polymeric materials at low frequencies. The hopping mechanism has been described and studied as a possible explanation for this kind of behavior 35 . FeVO 4 ‐PU/PMMA systems had substantially greater conductivity values, which were generally changed by the addition of FeVO 4 , which restored the conductivity's ability 21 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…universality law” may be used to characterize the typical behavior of AC conductivity in disordered solids and polymeric materials at low frequencies. The hopping mechanism has been described and studied as a possible explanation for this kind of behavior 35 . FeVO 4 ‐PU/PMMA systems had substantially greater conductivity values, which were generally changed by the addition of FeVO 4 , which restored the conductivity's ability 21 .…”
Section: Resultsmentioning
confidence: 99%
“…The hopping mechanism has been described and studied as a possible explanation for this kind of behavior. 35 FeVO 4 -PU/PMMA systems had substantially greater conductivity values, which were generally changed by the addition of FeVO 4 , which restored the conductivity's ability. 21 This trend suggests that the dopant molecules begin to bridge the gap as the dopant concentration rises.…”
Section: Conductivitymentioning
confidence: 93%
“…[4][5][6][7][8][9] The presence of such additives can also improve the mechanical properties and thermal stability of POM. Various nanollers have been examined for the preparation of POMbased nanocomposites, including nanosilica (NS), [4][5][6] carbon nanotubes, 7-9 montmorillonite, [10][11][12][13][14] CaCO 3 , 15 graphite, 16 Al 2 O 3 , 17 ZnO, 18 hydroxyapatite, 19,20 boehmite alumina, 14,21 polyhedral oligomeric silsesquioxane, 22,23 and NS and carbon bers. 24 POM can also been combined with ethylene-octene copolymer to improve the relaxation properties of POM.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the crystallization behavior of POM depends on its supramolecular structure [11,12]. However, POM has a linear molecular chains as (-CH 2 -O-) n structure which leads to high crystallinity, which limits its application [13][14][15]. Therefore, many studies have reported on the effect of additives on the crystallization performance of POM [16].…”
Section: Introductionmentioning
confidence: 99%